THE RELATION BETWEEN THE PROMOTION STRATEGY FROM DEPARTMENT OF COOPERATIVES AND SMALL MEDIUM ENTERPRISES AND THE DEVELOPMENT OF SMES IN MANADO - Kalonta, Keith; Lapian, S.L.V.H. Joyce; Worang, Frederik G. (FEB Universitas Sam Ratulangi Manado, 2016)
There are a variety of economic sectors that supporting economic growth in Indonesia. From some of the existing economic sectors, Small and Medium Enterprises sector has an important role and strategic in national economic development, both in terms of the amount of enterprises, in terms of job creation, as well as in terms of national economic growth as measured by Gross Domestic Product. Introducing or promotions become one of the important things that should be done by the government in an effort to develop existing SMEs, the objective of promotion in order that existing society can know and recognize existing SMEs. This research used qualitative research methodology. In this research, Department cooperatives and small medium enterprises and the owner of SMEs in Manado as the informant, the total informant are 8 people. The result of this research show that the Promotion Strategy for SMEs is very important, the promotion helpfully the SMEs for develop, with promotion the product or service from SMEs will know by people, and so many ways to do the promotion, used social media, print media, brochure, or join the exhibitions. For the government, must more give attention to promote the SMEs in Manado, and also the government must make a special website or application only for SMEs, so it can make easy for customer to buy or for SMEs to promote or sell their product Keywords: promotion strategy, small medium enterprises, department of cooperatives and SMEs